Alkali‐silica reaction performance testing of concrete considering external alkalis and preexisting microcracks. (8th May 2017) - Giebson, Colin; Voland, Katja; Ludwig, Horst‐Michael; Meng, Birgit
Abstract : In concrete elements, simultaneously subjected to cyclic loadings and external alkalis, the risk for damage caused by or under participation of an alkali‐silica reaction (ASR) is particularly high. This is of particular concern for concrete pavements due to the increasing heavy vehicle traffic and the application of sodium chloride (NaCl) de‐icer during winter. Since 2004, the climate simulation concrete prism test (CS‐CPT) has been used successfully to evaluate job mixtures for pavements by considering the impact of alkali‐containing de‐icers. However, the role of mechanical predamage on ASR is largely unclear. In a joint research project, the CS‐CPT has been used to investigate the influence of preexisting microcracks on ASR. It was evident that an ASR initiated earlier in the predamaged concrete prisms due to the more rapid ingress of NaCl solution through the microcracks.